Developmental Hints of Fairness Sensitivity: Current Investigations on Inequity Avoidance Inequity Avoidance - Büşra Aktaş (Psikoloji Çalışmaları)
Fairness-based decision-making is considered one of the most crucial topics in the literature on moral psychology. Previous findings have demonstrated that people make costly irrational decisions according to their level of fairness sensitivity. Moreover, individuals display inequity avoidance behavior by rejecting inequity favoring others (disadvantageous inequity) or themselves (advantageous inequity). According to developmental investigations, different mechanisms may underlie the display of advantageous or disadvantageous inequity avoidance. Previous studies have indicated that in various cultures, disadvantageous inequity avoidance follows a similar path, whereas advantageous inequity avoidance emerges at different ages. These findings have pointed out that socialization practices and cultural factors may be dominant in terms of the age of onset of advantageous inequity avoidance. In parallel, this review first presents the pioneer approaches to fairness in the recent literature on moral psychology and provides a summary of developmental studies that investigated inequity avoidance behavior by considering cultural differences. In summary, the literature has proposed that social context and reputational concerns may encourage children to adopt better strategies for displaying inequity avoidance with the increasing age. From this perspective, this notion was considered to lead to crosscultural differences in the developmental spectrum of behaviors particularly linked to advantageous inequity avoidance. This finding may be attributed to different social practices across cultures that are considered to play a functional role in reducing reputational concerns. Moreover, explanations based on collectivistic versus individualistic dual perspective are unable to explicate various specific dynamics for understanding the age of onset of the display of inequity avoidance behavior. Therefore, further studies are required to reveal the roles of specific socialization dynamics in the community, parental expectations, and widely accepted social interaction practices with relatives, which would largely contribute to the relevant literature.